Biocatalysis-driven CO2 valorization: Innovations and sustainable strategies in conversion and utilization - Lin Yuan; Emmanuel Mintah Bonku; Zhong-Hua Yang (Carbon Capture Science & Technology)
Anthropogenic CO2 emissions, a primary driver of global warming, necessitate innovative technologies to reconcile carbon neutrality with industrial growth. Biocatalysis, leveraging the precision of enzymatic systems, has emerged as a pivotal strategy for CO2 valorization within CO2 conversion and utilization (CCU) frameworks, enabling sustainable conversion of CO2 into platform chemicals and fuels. This review examines cutting-edge advances in biocatalytic CO2 conversion, with a focus on enzyme engineering breakthroughs that enhance catalytic efficiency and product selectivity. Key enzymes—including (de)carboxylases, carbon monoxide dehydrogenase, and formate dehydrogenases—are analyzed for their roles in CO2 fixation, alongside immobilization techniques that improve operational stability. Furthermore, sophisticated protein engineering approaches, including directed evolution and rational design, are emphasized for their potential to improve enzymatic performance through tailored modifications. By bridging molecular-scale innovations with system-level engineering, this work underscores biocatalysis as a multi-faceted solution for sustainable CO2 utilization. This contribution provides a comprehensive overview of current achievements and future perspectives in the field, emphasizing the role of biocatalysis in addressing global climate challenges.